Kemampuan Pemecahan Masalah Matematika Melalui Model Pembelajaran Kontekstual Berbantuan Quizizz Ditinjau dari Kecerdasan Visual Spasial - Ratnasari, Emiliana; Oktaviana, Dwi; Saputro, Marhadi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to determine whether there are differences in mathematical problem solving abilities through the contextual learning model assisted by Quizizz in terms of visual spatial intelligence. This research is a quantitative research type of True Experimental Design. The research subjects were class VIII students at SMPN 17 Pontianak with a total of 60 students. The samples in this study were class VIII B as an experimental class using the contextual learning model assisted by Quizzizz and class VIII A as a control class using a conventional learning model. Data was obtained from the mathematical problem-solving ability test given to students. The data analysis technique used a two-way anava test and an advanced test using a double comparison test with the Sheffe method. Based on the results of the analysis and discussion of the research data, the results were obtained that the ability to solve mathematical problems using the quizizz-assisted contextual learning model is better than the ability to solve mathematical problems using the conventional learning model. There is an interaction between the quizizz-assisted contextual learning model and students' spatial visual intelligence on mathematical problem solving